Empowerment of Village-Owned Business Entities (Bumdes) Baringin B Candi Laras District, Tapin Regency, South of Kalimantan Province - Aries Mardiono; Andi Tenri Sompa; M Riduansah Syafari (Wadah Inovasi Indonesia, 2022)
Empowerment in this case through the Empowerment of Village Owned Enterprises (Bumdes) is one part of sustainable development efforts. Today, the village is the basis of empowerment which is seen as the spearhead of the country's development at large. This study seeks to raise the issue of village empowerment, specifically the empowerment of Bumdes Orchid in Baringin B Village, Candi Laras Selatan District, Tapin Regency, South Kalimantan Province. Bumdes Anggrek, according to an initial interview with the village head of Baringin B, is the most advanced Bumdes in the Candi Laras Selatan sub-district, this Bumdes is even able to contribute to Village Original Income. However, the last few years, especially during the pandemic, have experienced a decline in income. Therefore, this study seeks to analyze how the Bumdes empowerment is and what obstacles it faces. The theory used in this research is the Village Empowerment Theory by Saragi, namely, there are six basic principles in village empowerment, including (1) Democratization of village life; (2) Sourced from local wisdom; (3) Community participation; (4) community empowerment; (5) Equality of opportunity; (6) Diversity. The method used in this study is a qualitative research method with a descriptive type, the technique of determining the informant is purposive. The results showed that the Bumdes Orchid could run well because of the support from various parties such as village officials, the BPD, the commitment of the management, and the community in general. The obstacles faced were environmental conditions such as facilities and infrastructure, the mindset community related to savings and loan habits as a Bumdes business unit that was not running smoothly, and the existence of a pandemic that caused economic problems for the community.